(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the influence of the cutting interval on gliricidia in relation to dry mass production, plant structure, crude protein (CP), neutral detergent insoluble fiber (NDF), acid detergent insoluble fiber (ADF), in vitro dry matter digestibility (DIVMS), nitrogen content and accumulation of the upper part (apex) and of the entire plant leaves. The experiment was carried out in the field in a randomized block design with three treatments and five replications. The treatments were composed in three different cut intervals, namely: T1 – two months; T2 – three months and T3 – four months. There was a significant difference (p ≤ 0.01) in gliricidia plants in total dry mass production. For the height of the gliricidia plants, it showed a significant effect for the four-month interval, when compared to the two- and three-month cutting interval. Analyzing gliricidia nitrogen at the apex, it was observed that there was no difference between treatments. The CP contents at the apex showed that there was no statistical difference between the treatments. The CP content in the treatment with a three-month interval between cuts in the leaves of the whole plant was superior to the other treatments. There were no significant differences in terms of NDF values between treatments at the apex. In turn, the NDF value in the leaves of the whole plant in the three-month interval between cuts treatment differed from the others. No significant differences were found between treatments regarding either the ADF at the apex or the ADF in the leaves of the whole plant. As for DIVMS values, there were no significant differences in the three treatments at the apex and leaves. It is concluded that the longer cutting interval provides greater productivity without affecting the nutritive value of the gliricidia apex. However, the cutting interval affected the CP and NDF contents in the leaves of the whole plant.